(3efGSc GdMLs - (3gGOj Hf YHGS Hf Ydj GHf cGTa GdZWGA, J (B1360(3g` (B1941(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj LYd HjJg ddESdGe YdeG (B... (3hbO QJHJg Ydi ebOeI hHGHjf hNGJeI(B. (3GdebOeI aj CehQ jfHZj JbOjegG hGdJfHjg YdjgG efgG Cfg jfHZj def YRe Ydi GdMLs
(3BNQgG (B:s
(3BNQgG(B: (3hCeG Yf GdKGfj aGdXGgQ ef GdCNHGQ LhGR GSJYeGdg ddhSGFO hGdeUGMa hddUHjGf ddJMQR hGdHQcI hdG jLhR GSJYeGdg deG jhLH EgGfI Ch gJcGs
(3jHOh CfgG eShOI GdeDda deG ajgG cTJ hTWH hJYOjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B8: 58s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis